The challenges with problem=based learning: a case study of MUFY students studying economics and information and communication technology (ICT) - Pratiba Narayanasamy, *; Seow, Esther * (Sunway College Kuala Lumpur, 2015)
Problem-based learning (PBL) is a method that challenges students to learn through engagement in a real scenario. It helps to develop problem solving strategies and disciplinary knowledge bases and skills by engaging students in an active role of problem solvers (Hmelo-Silver, 2004). The PBL approach originated from the medical school and is currently used in many different schools. This research paper is focused on the challenges of problem-based learning faced by students enrolled in the Monash University Foundation Year (MUFY) program offered in Sunway College, Malaysia. In order to carry out the research, two subjects which are Economics and Information and Communication Technology (ICT), are used. In today’s learning, PBL is considered an ideal learning approach which incorporates teamwork, independent learning, critical thinking and problem solving. Thus, the purpose of this research is to employ PBL and examine the challenges encountered by students learning using this problem-based approach.